Analysis of Long-Period Hazardous Waves in the Taiwan Marine Environment Monitoring Service - Doong, Dong-Jiing; Fan, Yang-Ming; Chen, Jin Yih; Kao, Chia Chuen (Frontiers in Marine Science, 2021)
A service platform (referred to as Taiwan Marine Environment Monitoring Service) was designed to integrate marine environmental parameters, including wind, wave, tide, current and temperature components, from in-situ and remote sensing observations, ship reports and numerical models to support the safety of various marine-related activities in Taiwanese waters. Independent modules were developed and plugged into the platform to facilitate advanced analyses via the safe sea, particle tracking module, extreme waves, oil spill simulation, tsunami warning (TW), sea level rise, dangerous swell warning (DSW), and SST drop modules. This paper introduces the service platform and DSW and TW module analysis methods. A real-time analysis method for tsunami height is developed and validated; a criterial analysis of hazardous swells is also performed. This service platform is now in operation and has served more than 10 governmental institutions and numerous members of the public in Taiwan.